1995
DOI: 10.1159/000188668
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Profile of Continuous Ambulatory Peritoneal Dialysis Patients

Abstract: Undernutrition in dialysis patients contributes to their morbidity and mortality. This is a cross-sectional study of the nutritional status of 61 patients treated with continuous ambulatory peritoneal dialysis (CAPD). They were studied with emphasis on assessment of their nutritional intake, anthropometric measurements, and evaluation of biochemical parameters. The correlation between the rate of CAPD peritonitis and these measurements was also examined. The majority of the patients (63.1%) had inadequate prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Prealbumin is excreted by the kidney via glomerular filtration [26] . Moreover, in previous studies [26] , [27] , recommendations for the routine use of serum prealbumin levels as a marker are tempered by the fact that prealbumin levels are increased in renal failure, presumably due to impaired degradation by the kidney [11] . These mechanisms may affect this negative correlation between prealbumin and residual renal function in our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prealbumin is excreted by the kidney via glomerular filtration [26] . Moreover, in previous studies [26] , [27] , recommendations for the routine use of serum prealbumin levels as a marker are tempered by the fact that prealbumin levels are increased in renal failure, presumably due to impaired degradation by the kidney [11] . These mechanisms may affect this negative correlation between prealbumin and residual renal function in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Serum prealbumin levels decline in response to inadequate protein intake and acute or chronic inflammation [10] . However, prealbumin levels may increase in renal failure, presumably because of impaired degradation by the kidney, and thus may not correlate with changes in other nutritional parameters [11] . Nonetheless, many studies have suggested that the serum prealbumin concentration is independently associated with mortality in hemodialysis patients, even after adjustment for other nutritional parameters including albumin [5] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Its impairment by inflammatory factors is involved in muscle proteolysis [ 49 ], but the serum concentrations are elevated in CKD patients [ 7 ]. It has been also been associated with malnutrition [ 54 ]. It was included here as a possible mediator of both inflammatory and metabolic derangements of uremic milieu.…”
Section: Methodsmentioning
confidence: 99%
“…In PD the problem of malnutrition [143] and decreased muscle mass [144] is well known. Since the marketing of AA-containing dialysis solutions, several studies have been reported.…”
Section: Treatment With Aasmentioning
confidence: 99%